Pregnancy in patients with tuberculosis: a TBNET cross-sectional survey. Issue 1 (December 2016) - Bothamley, Graham; Ehlers, Cordula; Salonka, Irina; Skrahina, Alena; Orcau, Angels; Codecasa, Luigi; Ferrarese, Maurizio; Pesut, Dragica; Solovic, Ivan; Dudnyk, Andrii; Anibarro, Luis; Denkinger, Claudia; et al.
Abstract Background Objectives: To determine whether the incidence of tuberculosis with pregnancy is more common than would be expected from the crude birth rate; to see whether there is significant delay in the diagnosis of tuberculosis during pregnancy. Method Design: A cross-sectional survey. Setting: 13 tuberculosis clinics within different European countries and the USA. Population/sample: All patients with tuberculosis seen at these clinics for a period > 1 year. Instrument: Questionnaire survey based on continuous data collection. Main outcome measures: number and proportion of women with tuberculosis who were pregnant; timing of diagnosis in relation to pregnancy, including those who were pregnant or delivered in the 3 months prior to the diagnosis of TB and those who developed TB within 3 months after delivery. Results Pregnancy occurred in 224 (1.5 %) of 15, 217 TB patients and followed the expected rate predicted from the crude birth rate for the clinic populations. TB was diagnosed more commonly in the 3 months after delivery (n = 103) than during pregnancy (n = 68;χ 2 = 25.1, P < 0.001). Conclusions TB is diagnosed more frequently after delivery, despite variations in local TB incidence and healthcare systems.